Answer:
x=4
Step-by-step explanation:
5
1
0
-4
Answer:
(-1,5)
Step-by-step explanation:
f(-1) = -2(-1)+3 = 2+3 = 5 replace x with the x value given in the ordered pair which is (-1, _) where x = -1
hope it helps.........
Answer:
a. The biomass weighs 2.30 * 10^7 kg after a year
b. It'll take 2.56 years to get to 4*10^7kg
Step-by-step explanation:
a.
k = 0.78,K = 6E7 kg
Given
dy/dt = ky(1- y/K)
Make ky dt the subject of formula
ky dt = dy/(1-y/K) --- make k dt the subject of formula
k dt = dy/(y(1-y/K))
k dt = K dy / y(K-y)
k dt = ((1/y) + (1/(K-y)))dy ---- integrate both sides
kt + c = ln(y/(K-y))
Ce^(kt) = y/(K-y)
Substitute the values of k and K
Ce^(0.78t) = y/(6*10^7 - y) ----- (1)
Given that y(0) = 2 * 10^7kg
(1) becomes
Ce^(0.78*0) = (2 * 10^7)/(6*10^7 - 2*10^7)
Ce° = (2*10^7)/(4*10^7
C = 2/7
Substitute 2/7 for C in (1)
2/7e^0.78t = y/(6*10^7 - y) ---(2)
We're to find the biomass a year later
So, t = 1
2/7e^0.78 = y/(6*10^7 - y)
0.62 = y/(6*10^7 - y)
y = 0.62(6*10^7 - y)
y = 0.62*6*10^7 - 0.62y
y + 0.62y = 0.62*6*10^7
1.62y = 0.62*6*10^7
1.62y = 3.72 * 10^7
y = 2.30 * 10^7kg.
Hence, the biomass weighs 2.30 * 10^7 kg after a year
b.
Here, we're to calculate the time it'll take the biomass to get to 4*10^7 kg
Substitute 4*10^7 for y in (2)
2/7e^0.78t = 4*10^7/(6*10^7 - 4*10^7)
2/7e^0.78t = 4*10^7/2*10^7
2/7e^0.78t = 2
e^0.78t = (2*7)/2
e^0.78t = 2
t = 2 * 1/0.78
t = 2.56 years
Hence, it'll take 2.56 years to get to 4*10^7kg
Answer: m=50w
Step-by-step explanation:
When you divide 900 by 18, you get 50.
Since we are trying to find the amount of minerals per worker, m is the first variable. w is the second because that is the number of workers you can get with the minerals Scarlett has.
So you would do 900÷18 to get the amount each worker is worth, which would be 50 minerals.
line.
Answer:
3 1/2
Step-by-step explanation:
|-7| - |-3 1/2| = 3 1/2
Answer:
Wideness ≈ 40 m
He will be able to do it .
Step-by-step explanation:
He wants to estimate the width of a river so he can get to the other side to save the world . The width of the river is the side AB. From the scale above 2 right angle triangle are formed . The smaller triangle is CDE and the larger triangle is CAB.
The angle ECD can be gotten below
tan C = opposite/adjacent
tan C = 8/6
tan C = 1.3333
C = tan⁻¹ 1.333
C = 53.1301022854
C = 53. 13°
∠ACB = ∠ECD (vertically opposite angles)
Using the angle to find the wideness of the river AB in triangle CAB.
tan C = opposite/adjacent
tan 53.13° = AB/30
AB = 30 tan 53.13
AB = 30 × 1.33332837108
AB = 39.9998511323
AB ≈ 40 m
He will be able to do it.